2010
DOI: 10.1007/s11096-010-9398-5
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of clozapine prescribing in a mental health service in New Zealand

Abstract: Contemporary management of patients with treatment resistant schizophrenia in New Zealand is broadly in line with national and international best practice guidelines. There is some evidence, based on hospitalisation rates, to support the assertion that shorter delays in accessing clozapine leads to better outcomes. This needs further evaluation using measures of clinical outcome including objective measures of functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 28 publications
4
33
0
Order By: Relevance
“…The use of clozapine varies enormously according to different countries and settings, with higher prescription rates in China 26 and Oceania 27 and lower in North America 28,29 . The rates of clozapine prescription for TRS patients found in Brazilian community centers were similar to rates found in studies carried out in the United States 28,29 , an especially low proportion when compared to other countries 26,27,30 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of clozapine varies enormously according to different countries and settings, with higher prescription rates in China 26 and Oceania 27 and lower in North America 28,29 . The rates of clozapine prescription for TRS patients found in Brazilian community centers were similar to rates found in studies carried out in the United States 28,29 , an especially low proportion when compared to other countries 26,27,30 .…”
Section: Discussionmentioning
confidence: 99%
“…However, studies indicate that adherence to this guideline is low (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Increasingly, longterm use of two or more regularly scheduled antipsychotics (polypharmacy) is prescribed, often before clozapine (11,15,(17)(18)(19)(23)(24)(25).…”
mentioning
confidence: 99%
“…Increasingly, longterm use of two or more regularly scheduled antipsychotics (polypharmacy) is prescribed, often before clozapine (11,15,(17)(18)(19)(23)(24)(25). This practice is inconsistent with evidence-based guidelines, which do not endorse long-term antipsychotic polypharmacy and recommend it only as a last-line treatment when clozapine has failed (6-10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In certain cases of non-response to clozapine, the use of other second-generation antipsychotics, augmentation strategies with antidepressants and/or mood stabilizers, combination of antipsychotics and electroconvulsive therapy have been suggested as treatment alternatives, however, with limited evidence for their efficacy [2,[21][22][23]. Despite this, it was reported that clinicians do often try other approaches before clozapine prescription and there could be long delays before prescription of clozapine [24,25]. In the present study, only 48.3% of the patients with TRS were reported to be currently on clozapine, which shows that majority of clinicians avoided prescribing clozapine despite the guidelines.…”
Section: Discussionmentioning
confidence: 99%